Penggunaan Bahasa Indonesia dalam Ceramah Ust. Muhammad Nuruddin - Muhammad Nurjana (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Da'wah is the process of conveying religious messages with the aim of inviting people to live in accordance with the provisions of Allah SWT and His Messenger. In the delivery of da'wah, language plays a vital role as an effective communication medium. The language used in da'wah must be gentle, polite, correct, and relevant to the audience so that the message can be received and understood. The history of the spread of Islam in Indonesia shows that the role of language is very significant in conveying the teachings of Islam, including language adaptation to local culture that facilitates public acceptance. Ustaz Muhammad Nuruddin is an example of a modern da'i who has succeeded in utilizing language as a medium of da'wah communication effectively. In his lecture entitled Year-End Reflection to Improve Self-Quality, he uses simple and easy-to-understand Indonesian, accompanied by a relaxed language style that attracts the audience. In addition, his method of delivering da'wah uses stories and analogies, which make it easier for worshipers to understand Islamic values in everyday life. This reflects that creativity, relevant language styles, and story-based approaches and analogies are the keys to successful da'wah in the face of diverse community backgrounds in the modern era.